(untitled) (Amsterdam,Boston, 2005)
Optical fiber telecommunications depend upon light traveling great distances through optical fibers. As light travels it tends to disperse and this results in some degree of signal loss. Raman amplification is a technique that is effective in any fiber to amplify the signal light as it travels through transmission fibers, compensating for inevitable signal loss. * First comprehensive guide to Raman amplification, a technique whose use has exploded since 1997 in order to upgrade fiber capacity; * Accessible to professionals just entering the field of optical fiber telecommunications; * Detailed enough for experts to use as a reference.
Keywords: Fiber optics.,Optical communications.,Optical amplifiers.,Raman effect.,Cấu trúc quang học,Máy khuếch đại quang học